A new species of Steleops Enderlein, and a Colombian record of S. pulcher New (Psocodea: ‘Psocoptera’: Psocidae) - Obando, Ranulfo González; Aldrete, Alfonso Neri García; Carrejo, Nancy Soraya (Zootaxa, 2011)
Steleops buitrerensis n. sp. is here described and illustrated; it constitutes the 14 th species known in the genus, the 12 th known in the neotropics, and the first in the genus to be recorded in Colombia. The forewings and antennae are sexually dimorphic, and the head pattern of coloration, as well as the genital structure, separates it from the other described species. The location of the types is indicated in the description, and a key is included to separate it from the other South American species. S. pulcher New, previously known only in Mato Grosso, Brazil, is here recorded in Colombia.